2015
DOI: 10.1016/j.echo.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations on the Use of Echocardiography in Adult Hypertension: A Report from the European Association of Cardiovascular Imaging (EACVI) and the American Society of Echocardiography (ASE)†

Abstract: Hypertension remains a major contributor to the global burden of disease. The measurement of blood pressure continues to have pitfalls related to both physiological aspects and acute variation. As the left ventricle (LV) remains one of the main target organs of hypertension, and echocardiographic measures of structure and function carry prognostic information in this setting, the development of a consensus position on the use of echocardiography in this setting is important. Recent developments in the assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
364
0
36

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 410 publications
(407 citation statements)
references
References 202 publications
7
364
0
36
Order By: Relevance
“…This latter finding may be explained by the high prevalence of obesity in JHS, and that defining LVH using LVM indexed to body surface area may obscure an association between BMI and LVH. [7, 33] In the current study, higher BMI was associated with a higher odds of eccentric and concentric hypertrophy when LVH was defined using LVM indexed to height 2.7 . Although a prior study by Fox et al[19] demonstrated that impaired fasting blood glucose was associated with a higher prevalence of concentric remodeling (p=0.05) among 1,512 African American women in the JHS cohort, the current study did not find an association between diabetes and elevated hemoglobin A1c levels with any of the three abnormal LV structural patterns.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This latter finding may be explained by the high prevalence of obesity in JHS, and that defining LVH using LVM indexed to body surface area may obscure an association between BMI and LVH. [7, 33] In the current study, higher BMI was associated with a higher odds of eccentric and concentric hypertrophy when LVH was defined using LVM indexed to height 2.7 . Although a prior study by Fox et al[19] demonstrated that impaired fasting blood glucose was associated with a higher prevalence of concentric remodeling (p=0.05) among 1,512 African American women in the JHS cohort, the current study did not find an association between diabetes and elevated hemoglobin A1c levels with any of the three abnormal LV structural patterns.…”
Section: Discussionmentioning
confidence: 59%
“…LVH was defined as LVMI ≥ 45 g/m 2.7 in females and ≥ 49 g/m 2.7 in males. [7, 30] A p-value <0.05 was considered to be statistically significant. Analyses were conducted using SAS version 9.4 (SAS Institute, Cary, NC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LVH can be caused by an adaptation of the myocardium to increased pressure or volume load, genetic mutations or systemic conditions, as summarized in Table 1 3)4)5)6)7)8)9)10)11)12)13)14)15)16). LVH develops gradually, and therefore patients remain asymptomatic in early stages.…”
Section: Introductionmentioning
confidence: 99%
“…LVH develops gradually, and therefore patients remain asymptomatic in early stages. When the condition progresses, symptoms related to diastolic and systolic dysfunction ultimately bring the patient to the clinic 6). Analysing the grade of LVH severity is of great importance to clinical practice in terms of prognosis and treatment choices.…”
Section: Introductionmentioning
confidence: 99%